1983
DOI: 10.1111/j.1439-0434.1983.tb00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Antagonistic Fluorescent Pseudomonas spp. and their Root Colonization and Persistence following Treatment of Seed Potatoes

Abstract: One hundred and twelve fluorescent Pseudomonas isolates from potato periderm were screened for antagonistic activity in vitro against 5 pathogenic and saprophytic fungi, 5 Gram‐positive bacteria including Streptomyces scabies and 4 Gram‐negative bacteria including Erwinia car. var. carotovora and Erwinia car. var. atroseptica. Fifty‐seven percent of the isolates showed wide spectrum inhibitory activity, mostly due to the production of fluorescent siderophores. Only 4 % of the isolates were very strong antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(115 citation statements)
references
References 28 publications
1
113
0
1
Order By: Relevance
“…Studies made by other workers have also observed a population revival when seed bearing apparently declining bacterial numbers are introduced into the soil environment. Geels and Schippers (1983) demonstrated that even after large decreases in viable cell numbers during drying of treated potato seed tubers, bacterial numbers subsequently increased substantially during the first three d after sowing. The general trend in rhizosphere population dynamics with bacteria introduced as seed treatments is typified by a rapid increase in numbers (especially in sterile soil) followed by a period of stabilization and slow decline to non-detectable levels (Geels and Schippers 1983;Kloepper et al 1992;Kluepfel and Tonkyn 1992;Kluepfel 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies made by other workers have also observed a population revival when seed bearing apparently declining bacterial numbers are introduced into the soil environment. Geels and Schippers (1983) demonstrated that even after large decreases in viable cell numbers during drying of treated potato seed tubers, bacterial numbers subsequently increased substantially during the first three d after sowing. The general trend in rhizosphere population dynamics with bacteria introduced as seed treatments is typified by a rapid increase in numbers (especially in sterile soil) followed by a period of stabilization and slow decline to non-detectable levels (Geels and Schippers 1983;Kloepper et al 1992;Kluepfel and Tonkyn 1992;Kluepfel 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Geels and Schippers (1983) demonstrated that even after large decreases in viable cell numbers during drying of treated potato seed tubers, bacterial numbers subsequently increased substantially during the first three d after sowing. The general trend in rhizosphere population dynamics with bacteria introduced as seed treatments is typified by a rapid increase in numbers (especially in sterile soil) followed by a period of stabilization and slow decline to non-detectable levels (Geels and Schippers 1983;Kloepper et al 1992;Kluepfel and Tonkyn 1992;Kluepfel 1993). Kluepfel (1993) reported that for a fluorescent pseudomonad seed treatment, regardless of the initial concentration of inoculum applied (within a range of 10 4 -10 9 cells ml -1 ), an optimum rhizosphere population potential was reached which represented the carrying capacity of the root.…”
Section: Discussionmentioning
confidence: 99%
“…In duplicate, roots of six plants per treatment were harvested, weighed, and shaken vigorously for 1 min in 5 mL of 10 mM MgSO 4 containing 0.5 g of glass beads (0.17 mm diameter). Appropriate dilutions were plated onto King's medium B agar supplemented with cycloheximide (100 mg/L), ampicillin (50 mg/L), chloramphenicol (13 mg/L), and rifampicin (150 mg/L), which is selective for rifampicin-resistant, fluorescent Pseudomonas spp (Geels and Schippers, 1983). After overnight incubation at 28ЊC, the number of rifampicin-resistant colony-forming units per gram of root fresh weight was determined.…”
Section: Rhizosphere Colonizationmentioning
confidence: 99%
“…Densities on the rhizoplane of the aerobic bacteria, of the total fluorescent pseudomonads and of strains WCS417r or B4, were evaluated by numeration of colonyforming units (c.f.u.) after plating (Spiral System®, Interscience, France) serial dilutions of the rhizoplane suspensions on Bacto peptone agar supplemented with 100 ppm cycloheximide (BP^), on KB"â gar (Geels & Schippers, 1983) and on KB"^ agar supplemented with 150 ppm rifampicin, respectively. Colonization within the root was assessed from 16 replicate plants.…”
Section: Colonization Assay With Roots Grown In Rock Woolmentioning
confidence: 99%